Outcomes of Pediatric Liver Transplantation in Korea Using Two National Registries - Hong, Suk Kyun (J Clin Med, 2020)
Background: This retrospective study aimed to evaluate overall survival and the risk factors for mortality among Korean pediatric liver transplantation (LT) patients using data from two national registries: the Korean Network Organ Sharing (KONOS) of the Korea Centers for Disease Control and Prevention and the Korean Organ Transplantation Registry (KOTRY). Methods: Prospectively collected data of 755 pediatric patients who underwent primary LT (KONOS, February 2000 to December 2015; KOTRY, May 2014 to December 2017) were retrospectively reviewed. Results: The 1-, 5-, 10-, and 15-year survival rates were 90.6%, 86.7%, 85.8%, and 85.5%, respectively, in KONOS, and the 1-month, 3-month, 1-year, and 2-year survival rates were 92.1%, 89.4%, 89.4%, and 87.2%, respectively, in KOTRY. There was no significant difference in survival between the two registries. Multivariate analysis identified that body weight ≥6 kg (p <0.001), biliary atresia as underlying liver disease (p = 0.001), and high-volume center (p < 0.001) were associated with better survival according to the KONOS database, while hepatic artery complication (p < 0.001) was associated with poorer overall survival rates according to the KOTRY database. Conclusion: Long-term pediatric patient survival after LT was satisfactory in this Korean national registry analysis. However, children with risk factors for poor outcomes should be carefully managed after LT.